God is not nice: rejecting pop culture theology and discovering the God worth living for - Lehner, Ulrich L. (Ave Maria Press, 2017)
An image of God that isn't true -- The God of creation -- The God of no use -- The God of our imagination -- The God of thunder -- The God of terror -- The God of surrender -- The God of intimacy -- The God of consolation -- The God of incarnation -- The God of rebirth -- The adventurous God